Prevalence of type 2 diabetes mellitus (T2DM) in the adult Russian population (NATION study). (May 2016) - Dedov, Ivan; Shestakova, Marina; Benedetti, Massimo Massi; Simon, Dominique; Pakhomov, Iakov; Galstyan, Gagik
Abstract: Aim: To estimate type 2 diabetes mellitus (T2DM) prevalence in Russian adults. Methods: NATION is a national, epidemiological, cross-sectional study, conducted in Russia. In adults (aged 20–79 years), recruitment was stratified by age, sex, geographic region and settlement type to obtain a representative sample. Recruitment was in public areas with high numbers of people. T2DM was diagnosed by glycated haemoglobin A1c (HbA1c) levels (diabetes: HbA1c ≥6.5% [≥48 mmol/mol]; pre-diabetes: HbA1c ≥5.7 to <6.5% [≥39 to <48 mmol/mol]). Socio-demographic and anthropometric data were collected. Results: Blood samples from 26, 620 subjects were available. Overall, 5.4% were diagnosed with T2DM (previously diagnosed: 2.5%; previously undiagnosed: 2.9%); 19.3% were pre-diabetic. T2DM prevalence increased with age (up to 70 years) and was higher among females than males (6.1% vs. 4.7%, p < 0.001). The estimated proportion of subjects with pre-diabetes and T2DM tended to increase with increasing body mass index. T2DM prevalence was higher in rural versus urban populations (6.7% vs. 5.0%, p < 0.001). Conclusion: In the Russian adult population, 19.3% had pre-diabetes, T2DM prevalence was 5.4%, and 54% of subjects with diabetes were previously undiagnosed. These results may help to develop a new T2DM predictive, preventative and management programme in Russia.